The Strategic Impact of META-NET on the Regional, National and International Level - Rehm, Georg (Array, 2014)
This article provides an overview of the dissemination work carried out in META-NET from 2010 until early 2014 ; we describe its impact on the regional, national and international level, mainly with regard to politics and the situation of funding for LT topics. This paper documents the initiative’s work throughout Europe in order to boost progress and innovation in our field.